Self-Reported Oral Hygiene Habits amongst Visually Impaired Students - Nayak, Prahi; Mathur, Aditi; Shetty, Neema; Makhijani, Barkha; Bali, Ashish; Manohar, Balaji (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Introduction: Good oral hygiene provides a basis for good oral health and is important for prevention and treatment of oral conditions in children. Hence, it is essential to provide knowledge and treatment at regular intervals to the visually impaired individuals. Objective: To evaluate the oral hygiene practices of visually impaired students attending a blind school with the help of a questionnaire. Methods: The oral hygiene practices were evaluated in visually impaired students between the ages of 6 years to 22 years. A total of 92 students were enrolled from a blind school in Udaipur. The oral hygiene practice was assessed by a questionnaire survey. Results: About 96.7% of the students brushed their teeth daily out of which 94.3% brushed their teeth with the help of a toothbrush and toothpaste. Majority of them brushed once a day in the morning. A total of 39.1% of the students cleaned their tongue also. All the students brushed alone without any guidance or supervision. Conclusion: Although the blind students cannot see, they still practice good oral hygiene.